289 Effects of informative videos to empower parents in handling acutely ill children: a randomized controlled trial. (1st May 2022) - Borch-Johnsen, L; Gren, C; Lund, S; Folke, F; Schrøder, M; Frederiksen, MS; Baastrup, M; Lippert, F; Ersbøll, AK; Greisen, G; Cortes, D
Abstract : Background: Copenhagen Emergency Medical Services (CEMS), Denmark, serves the Capital Region and receives about 200, 000 out-of-hours calls/year regarding children. About 40% are referred for further assessment at hospital, but less than two thirds of these children need medical treatment. We studied if parents could be empowered in handling children with mild symptoms at home by informative videos, and thereby reduce hospital admissions. Method: A prospective randomized controlled trial was conducted from 13th October, 2020 – 2nd December, 2021. Parents who called CEMS with children aged 0.5–11.9 years were offered access to informative videos before reaching telephone triage. Parents who accepted were randomized to intervention (receiving videos only) or control (standard telephone triage). Parents could repeat call for triage. Both groups received an electronic survey including questions on self-efficacy the following day. Hospital charts were reviewed blinded to randomization for hospital referrals within 72 hours. Main outcomes were high self-efficacy score and delayed hospital admissions or deaths. Secondary outcomes were treatment, duration of hospitalization, and number of engaged users of the videos. Results: A total of 4687 children were included. Only data from preliminary analysis of the first 400 surveys is available now. The self-efficacy-score was high in 84.7% (149/176) of the intervention group and in 82.7% (167/202) of the control group (p=0.68). There were no delayed admissions or deaths caused by the videos. Conclusion: Preliminary results showed equally high score of self-efficacy of parents in both groups. The use of videos appeared to be safe. Conflict of interest: None. Funding: This project was funded by TrygFonden, Denmark, Copenhagen University Hospital—Amager and Hvidovre, Copenhagen, Denmark and the Capital Region, Denmark.